Business systems analysis and design - Davis, William S. (Wadsworth series in management information systems, 1994)
Aimed at systems analysis and design courses generally taught in business departments, this text focuses on such issues as management implications, the link between systems analysis/design and the organization's strategic information needs and the complexity of modern systems. The book follows the traditional system development life cycle, and key tools and techniques are presented in the context of that life cycle.